Moderasi Sustainable Governance atas Pengaruh Governance Risk Management and Compliance, Enterprise Resource Planning, Growth Opportunity Terhadap Kinerja Perusahaan - Sugiyanto, Sugiyanto; Nurzaman, E; Kartolo, Rachmat; Febrianti, Fitri Dwi (Universitas 17 Agustus 1945 Jakarta, 2025)
Enterprise Resource Planning Business opportunities in the modern era are rapidly evolving, with significant growth in Indonesia’s business sector. In this context, strong company performance is a crucial consideration. Sustainable Governance represents the continuity of corporate objectives, aiming to meet the expectations of both investors and stakeholders. This study aims to examine and analyze the moderating role of Sustainable Governance in the relationship between Governance, Risk Management, and Compliance (GRC), Enterprise Resource Planning (ERP), and Growth Opportunity on Company Performance (a study of financial sector companies listed on the Indonesia Stock Exchange during the period 2019–2024). This research is quantitative in nature. Samples were selected using purposive sampling based on predefined criteria. The methods used include descriptive statistical analysis, Chow test, Hausman test, and multiple Lagrange multiplier tests to determine the appropriate model. Further analyses involved classical assumption testing, panel data regression, and Moderated Regression Analysis (MRA). The study utilized 110 secondary data entries and was conducted using E-Views 12 software. The results indicate that the selected model is the Fixed Effect Model (FEM). Simultaneous hypothesis testing shows that Sustainable Governance, GRC, ERP, and Growth Opportunity collectively influence company performance. The t-test results reveal that GRC does not have a significant effect on company performance, while ERP has a significant positive effect. In contrast, Growth Opportunity does not significantly affect company performance. Moderation test results show that Sustainable Governance strengthens the relationship between GRC and company performance, while it weakens the relationship between ERP and company value.